(untitled) (Anclajes, 2020)
This article analyzes several short stories and essays written by Argentine writer Néstor Perlongher, reflecting on the connection that his prose writing had with sexuality, economics, and politics. It explores the rise of desire in Perlongher’s work via its post-structuralist tone, examining the link between the affinity with the capitalist system and the crisis of old discursive patterns and critical debates of the 1980s.